Silver Atomic Quantum Clusters of Three Atoms for Cancer Therapy: Targeting Chromatin Compaction to Increase the Therapeutic Index of Chemotherapy. Issue 33 (3rd July 2018) - Porto, Vanesa; Borrajo, Erea; Buceta, David; Carneiro, Carmen; Huseyinova, Shahana; Domínguez, Blanca; Borgman, Kyra J. E.; Lakadamyali, Melike; Garcia‐Parajo, Maria F.; Neissa, José; García‐Caballero, Tomás; Barone, Giampaolo; et al.
Abstract: Nanomaterials with very low atomicity deserve consideration as potential pharmacological agents owing to their very small size and to their properties that can be precisely tuned with minor modifications to their size. Here, it is shown that silver clusters of three atoms (Ag3 ‐AQCs)—developed by an ad hoc method—augment chromatin accessibility. This effect only occurs during DNA replication. Coadministration of Ag3 ‐AQCs increases the cytotoxic effect of DNA‐acting drugs on human lung carcinoma cells. In mice with orthotopic lung tumors, the coadministration of Ag3 ‐AQCs increases the amount of cisplatin (CDDP) bound to the tumor DNA by fivefold without modifying CDDP levels in normal tissues. As a result, CDDP coadministered with Ag3 ‐AQCs more strongly reduces the tumor burden. Evidence of the significance of targeting chromatin compaction to increase the therapeutic index of chemotherapy is now provided. Abstract : Ag3 clusters (Ag3 ‐AQCs), produced by an efficient ad hoc method, provide evidence of the significance of targeting chromatin compaction to increase the therapeutic index of chemotherapeutic drugs. Coadministration of Ag3 ‐AQCs increases the cytotoxic effect of DNA‐acting drugs on human lung carcinoma cells without modifying their levels in normal tissues and strongly reduces the tumor burden.